Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed